A Scopus-Based Bibliometric Landscape of Cybersecurity Research (2000–2026): Trends, Collaboration, and Research Directions - Judijanto, Loso (West Science Information System and Technology, 2026)
The rapid advancement in digital technologies has resulted in a significant increase in the importance of cybersecurity, resulting in an upsurge in the number of studies conducted in this domain during the last two decades. Therefore, the present work is intended to investigate the intellectual structure, collaboration patterns, and evolution of themes in cybersecurity research through a bibliometric analysis. Data have been extracted from Scopus from the time period 2000-2026, and VOSViewer has been used to conduct the visualization process through the identification of the co-authorship network, citation network, and keywords co-occurrence network. As observed from the results obtained, there are a few dominant countries contributing to cybersecurity research, including the US, India, and China that play the roles of central hubs in the network of collaborations. It can be found from the citation network analysis that highly cited papers deal extensively with artificial intelligence, machine learning, and deep learning as they play a crucial role in cybersecurity research. Finally, through keyword analysis, it has been revealed that there is a transition in theme from intrusion detection and network security to newer themes such as artificial intelligence-based security, blockchain, Internet of Things (IoT), and behavioral cybersecurity. This study contributes to the literature by providing a comprehensive overview of the evolution and current state of cybersecurity research, while also identifying emerging trends and potential directions for future studies.